(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some observations on activity and behaviour of Lyctocoris campestris (F.) (Heteroptera Anthocoridae), a predator of stored product insects, are reported. The anthocorid was found in association with insects infesting stores of Triticum spelta L. in Central Italy.